pH-induced in situ gelling systems of indomethacin for sustained ocular delivery - Thilek Kumar M.; Bharathi D.; Balasubramaniam J.; Kant S.; Pandit J.K. (My University, 2025)
The low bioavailability and ocular residence time exhibited by the topical conventional liquid opht halmic formulations because of spillage by overflow, dilution of drug by tear turn over, nasolacrimal drainage and systemic absorption may be overcome by the use of in situ forming systems that are instilled as liquid drops into the cul-de-sac of the eye, where they transform into a gel or semisolid phase. The present work describes the formulation and evaluation of an opthalmic delivery system of an antiinflammatory drug, indomethacin for the treatment of uveitis based on the concept of pH induced in situ gelation. The carbopol solutions which are acidic and less viscous, transform into stiff gels upon increase in pH of eyes as the gelling agents and its combination with hydroxypropylmethylcellulose-K15M, a well known ocular viscosity enhancing agent. The enhanced therapeutic efficacy and sustained release of indomethacin over 8 hour period in vitro make them an excellent candidate for in situ gelling ocular delivery systems.